The Influence of Bank Health Levels on Share Prices in Conventional General Banking Listed on the Indonesian Stock Exchange for the Period 2019 – 2022 - Richad Alamsyah; Wulan Wahyuni RP; Nilda Tartilla (MultiTech Publisher, 2023)
This research purpose is to analyze the impact of bank soundness on stock price both simultaneously and partially. This research conducted on several indicators which represented by each ratio. There are risk profile represented by Non Performing Loan (NPL), earning represented by Return on Asset (ROA), and capital represented by Capital Adequacy Ratio (CAR). The population was conventional banking companies listed on Indonesia Stock Exchange during 2019-2022. Sampling method used in this research was purposive sampling and obtained 36 banking companies as a sample. This research using quantitative method. Analysis technique used in this reseach was multiple linier regression. The result shows that simultaneously NPL, ROA, CAR have significant effect on stock price. Partially there was a significant and positive effect between ROA and stock price. However, Partially there was a significant and Negative effect between NPL, CAR and stock price